Nesting behavior, taxonomic notes and potential distribution of Paratrigona eutaeniata (Hymenoptera: Apidae, Meliponini) - FERNÁNDEZ, DIANA CATALINA; ZAMBRANO-G., GISELLE; GONZALEZ, VICTOR H. (Revista Colombiana de Entomología, 2010)
The nesting habits of stingless bees in the genus Paratrigona are diverse and still unknown for most of the species. Herein we present information on these aspects and on the taxonomy of P. eutaeniata in the southwestern Andes of Colombia. To date, this species has been considered restricted to the Andean and sub-Andean forests of the western slopes of the Cordillera Oriental, in northern Colombia. We describe and illustrate for the first time the internal nest architecture, the queen, and morphological variations of the worker and the male. We also used a species distribution model to predict the potential distribution of P. eutaeniata in northwestern South America.